Diagnostic value of IgG isotype responses against Brugia malayi antifilarial antibodies in the clinical spectrum of brugian filariasis - Wongkamchai S. (2014)
To study the diagnostic significance of antifilarial IgG subclasses in the clinical spectrum of brugian filariasis, IgG1, IgG3 and IgG4 antifilarial antibodies were determined in an exposed population comprising 74 asymptomatic amicrofilaraemics, 30 microfilaraemics, 20 lymphangitis and 16 elephantiasis patients resident in Narathiwart province, an area endemic for Brugia malayi lymphatic filariasis in southern Thailand. The dominant isotype of antifilarial antibody was IgG4. A significantly higher percentage of individuals were positive for IgG1 in the microfilaraemic and lymphangitis groups compared with the elephantiasis and endemic normal patients, while a significantly higher positive rate of IgG3 was found in those with lymphangitis. The possible role of these isotypes for diagnostic purposes and the pattern of antibody response in various clinically manifesting groups are discussed.